An archaeological reconstruction of Saqqaq bows, darts, harpoons, and lances - Grønnow, Bjarne (Études/Inuit/Studies, 2012)
AbstractPermafrost-preserved materials from two Saqqaq sites (ca. 3900-2600 BP) in Disko Bay, West Greenland, have provided unique insight into woodworking in the early Arctic Small Tool tradition. Use of driftwood played a decisive role in the complex material culture of Saqqaq society, and analyses of more than 15,000 artifacts, fragments, and wood shavings enable us to reconstruct the woodworking processes and all categories of toolkits. This article presents an archaeological reconstruction of the remarkably diverse and technologically advanced Saqqaq hunting toolkit, which includes darts, harpoons, lances, and bows and arrows—among the earliest preserved specimens in the New World.